2022
DOI: 10.1186/s43556-022-00098-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of therapeutic vaccines for the treatment of diseases

Abstract: Vaccines are one of the most effective medical interventions to combat newly emerging and re-emerging diseases. Prophylactic vaccines against rabies, measles, etc., have excellent effectiveness in preventing viral infection and associated diseases. However, the host immune response is unable to inhibit virus replication or eradicate established diseases in most infected people. Therapeutic vaccines, expressing specific endogenous or exogenous antigens, mainly induce or boost cell-mediated immunity via provokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 223 publications
0
24
0
Order By: Relevance
“…COVID-19 vaccine, expressing specific antigens, mainly induces humoral immunity via activating B lymphocytes to produce specific antibodies or elicit cell-mediated immunity via provoking cytotoxic T-cells. 56 Previous studies have reported that cancer patients have lower seroconversion rates after complete vaccination compared to healthy controls. 57 Immunocompromised cancer patients may have an inadequate immune response after COVID-19…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 vaccine, expressing specific antigens, mainly induces humoral immunity via activating B lymphocytes to produce specific antibodies or elicit cell-mediated immunity via provoking cytotoxic T-cells. 56 Previous studies have reported that cancer patients have lower seroconversion rates after complete vaccination compared to healthy controls. 57 Immunocompromised cancer patients may have an inadequate immune response after COVID-19…”
Section: Discussionmentioning
confidence: 99%
“…As discussed earlier (Sec.4), in therapeutic vaccines (and also in antigen-specific immunotherapy via homeopathic medicines), T-cell mediated (cellular) immunity plays the central role [43][44][45].…”
Section: Why Are Dilution and Dosage Important In Homeopathy?mentioning
confidence: 95%
“…If the specific homeopathic medicine is given to the patient, an unfavourable outcome is expected because the administration of antigens similar to the antigens of a pathogen to a patient, who is already infected with the very pathogen, should be counterproductive. However, such counterintuitive idea is utilized in therapeutic vaccines or vaccine therapy, a type of antigen-specific immunotherapy, which has been in the limelight in recent years for the treatment of cancers, autoimmune and infectious diseases [43,44]. In vaccine therapy, the administration of the antigens of a pathogen to a patient, who is already infected with the pathogen, helps in curing or alleviating the existing disease (as opposed to prophylactic vaccines used for the prevention of disease).…”
Section: How Can Homeopathic Therapy Be Understood As An Antigen-spec...mentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in genetic engineering and monoclonal antibody production have markedly improved the treatment success rates for a wide range of cancers, infectious diseases, and autoimmune diseases 4 . Compared with low molecular weight compounds, antibody (Ab) drugs have several advantages, including high specificity and affinity, good stability in the blood stream, and a long half‐life, which means that a single administration often has long‐lasting therapeutic efficacy with reduced side effects 5 .…”
Section: Introductionmentioning
confidence: 99%